Deep Learning Based Learning Management at Nur Syamsiyani Islamic Elementary School, Bintang Meriah Village, Batang Quiz - Safran Safran; Erni Suyani (Intiqad: Jurnal Agama dan Pendidikan Islam, 2026)
The development of artificial intelligence and the demands of 21st-century learning underscore the urgency of implementing immersive learning in elementary schools so that students not only master the material but also think critically, analytically, and contextually. This study aims to analyze immersive learning management at Nur Syamsiyani Islamic Elementary School, including planning, implementation, evaluation, and supporting and inhibiting factors. A descriptive qualitative approach was used, with data collected through observation, in-depth interviews, and documentation studies. Data analysis was conducted in accordance with the Miles, Huberman, and Saldana model. The results show that teachers have integrated immersive learning principles through HOTS-based objective design, the use of PjBL, PBL, and Inquiry models, and authentic assessment. This approach positions students as active actors involved in exploration, collaboration, and problem-solving. Evaluation is conducted holistically through portfolios, process observations, and reflection. Supporting factors include teacher creativity, principal support, the flexibility of the Independent Curriculum, and a supportive classroom environment. Existing barriers include limited time, facilities, and differences in student abilities. This study emphasizes the importance of systematic and adaptive learning management to strengthen deep learning practices in elementary schools and recommends further research on developing implementation models for more diverse Islamic school contexts.